1978
DOI: 10.2466/pr0.1978.42.3.891
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Lunacy: A Review

Abstract: A historical account of the concept of lunacy in terms of its symptomatology and aetiological models, and a critical review of its validity and reliability are given. It is concluded that there is no unequivocal support for a belief in a lunar influence on human behaviour and that any future research should be directed towards the specification of the behaviour and people that might be affected by the phases of the moon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Seven years have elapsed since Campbell and Beets (1978) concluded that “lunar phase is not related to human behavior” (p. 1123). Their conclusion is similar to those reached by astronomers (Abell & Singer, 1981), physicists (Culver & Ianna, 1979), and other psychologists (Coles & Cooke, 1978; Cooke & Coles, 1978). Further, books championing the lunar hypothesis have received skeptical and, in a few cases, hostile reviews (Abell, 1979; Earley, 1978; Ornstein, 1978; Rotton, 1982a).…”
supporting
confidence: 83%
“…Seven years have elapsed since Campbell and Beets (1978) concluded that “lunar phase is not related to human behavior” (p. 1123). Their conclusion is similar to those reached by astronomers (Abell & Singer, 1981), physicists (Culver & Ianna, 1979), and other psychologists (Coles & Cooke, 1978; Cooke & Coles, 1978). Further, books championing the lunar hypothesis have received skeptical and, in a few cases, hostile reviews (Abell, 1979; Earley, 1978; Ornstein, 1978; Rotton, 1982a).…”
supporting
confidence: 83%
“…The value of x,2 of 40.74 ( p < ,001) supports the hypothesis that the different occupational groups believed lunar cycles affect human behavior. DISCUSSION Although numerous studies have disconfirmed the lunacy hypothesis (Abell & Singer, 1981;Campbell, 1982;Campbell & Beets, 1978;Coles & Cooke, 1978;Cooke & Coles, 1978;Culver & Ianna, 1988;Culver, Rotton, & Kelly, 1988;Rotton & Kelly, 1985), apparently, the belief is st111 widely accepted and so can influence decision-making of those who hold the belief. Such a belief might inadvertently impair the judgement of mental health workers; however, the extent to which this occurs is not known.…”
Section: Resultsmentioning
confidence: 93%
“…To locate studies on lunar effects on the timing of completed suicide, we used a variety of literature search strategies: (i) appropriate keywords ({suicide OR suicidal} AND {moon OR lunar}) entered in the essential electronic literature databases (ISI Web of Knowledge, PubMed, and PsycINFO; up to early 2008); (ii) cited reference searches of retrieved studies in ISI Web of Knowledge; (iii) mining of reference lists of retrieved studies; (iv) consultation of relevant research reviews on the topic [1,[3][4][5][6][7][8]; and (v) consultation of major reviews and topical textbooks and handbooks of suicidology [12][13][14][15][16][17]. These combined search strategies yielded 15 reports, published between 1964 and 2005 [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%